2015
DOI: 10.1080/01694243.2015.1004507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2% chlorhexidine gluconate cavity disinfectant on microtensile bond strength of tooth-coloured restorative materials to sound and caries-affected dentin

Abstract: This study evaluated the effect of 2% chlorhexidine gluconate based cavity disinfectant (CHX) on the microtensile bond strength (µTBS) of glass ionomer, resin-modified glass ionomer and packable resin composite to sound and caries-affected dentin. Sound and occlusal caries-affected human third molars (N=36, n=3 per group) were randomly divided into three experimental groups to receive one of the following restorative materials; a) Glass ionomer (Ketac Molar, 3M ESPE; GI), b)Resin-modified glass ionomer (Vitrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
2
3
1
Order By: Relevance
“…The bond strength tests did not show a significant difference between the positive control (CHX) and the negative control (NT). These data are consistent with other studies that have reported the absence of damage to the bond strength of the dentin/resin interface after application of 2% CHX as a cavity disinfectant [ 66 , 67 ]. Carrilho et al [ 68 ] showed that significant amounts of CHX were retained in dentin independently of the dose of CHX applied (0.2, 2%) or the time (from 30 min to 8 weeks).…”
Section: Discussionsupporting
confidence: 93%
“…The bond strength tests did not show a significant difference between the positive control (CHX) and the negative control (NT). These data are consistent with other studies that have reported the absence of damage to the bond strength of the dentin/resin interface after application of 2% CHX as a cavity disinfectant [ 66 , 67 ]. Carrilho et al [ 68 ] showed that significant amounts of CHX were retained in dentin independently of the dose of CHX applied (0.2, 2%) or the time (from 30 min to 8 weeks).…”
Section: Discussionsupporting
confidence: 93%
“…As per the observations made in this study, it could be stated that 2% CHX was the only cavity cleanser that did not significantly reduce the bond strength of RMGIC to dentin. This was in accordance with the study by Cunningham, et al ( 3 ), Aykut-Yetkiner, et al ( 23 ), and Ersin, et al ( 24 ). The reason for the insignificant reduction in the SBS of RMGIC in Group III could be because of the negligible interference in the setting reaction of GIC by CHX.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the application of CHX did not affect the bond strength of GIC to dentin compared to the control group which was in line with the findings of a previous study. 24 Moreover, in this study, the µSBS of the group in which CHX was applied after the conditioner was more than that of the group in which CHX was applied before the conditioner, albeit the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 56%
“…These include the removal of the smear layer and surface contaminants, alteration of the surface free energy and the wettability of dentin, partial demineralization of the dentin surface, and the exposure of the dentin collagen network which might result in the close adaptation of the nanoparticles to dentin surfaces and the better diffusion of these small size molecules into a partially demineralized tooth structure. 24,37 Nanoparticles diffused between partially demineralized collagen fibers might increase the surface free energy previously reduced by the partial demineralization of dentin resulting from applying the conditioner. 37 However, the effects of the nanoparticles on the free energy and wettability of the dentin surface were not evaluated in this study and should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%